PENGAWASAN TERHADAP LEGALITAS PASPOR DALAM RANGKA PENCEGAHAN TKI NONPROSEDURAL DI KANTOR IMIGRASI KELAS 1 TPI MALANG - Agista, Lara (Jurnal Ilmiah Kajian Keimigrasian, 2023)
This study analyzes the forms of supervision and policies on the legality of passports as a requirement for Indonesian immigration cross-border travel documents. As part of efforts to realize Indonesian policies, monitoring of the legality of passports is one way to detect invalid forms of forging passport data. The problem of research is how the sanctions are against perpetrators of falsifying data on illegal passport ownership and monitoring the legality of passports for Indonesian citizens and foreigners at the Immigration Office Class 1 TPI Malang. The method in this study uses the document study method, which utilizes secondary data obtained from relevant journals, books, newspapers, and websites. And also conduct field studies directly at the immigration office class 1 TPI Malang to find out how the surveillance measures and policies against illegal passports. The results of this study indicate that the existence of criminal law and accountability for perpetrators who are included in the elements of a criminal act will be asked for criminal responsibility in a juridical manner. Keywords: Passport, illegal, criminal sanctions